Culture and Identity in International Relations: Re-Thinking Javanese Value In Contemporary Indonesian Multilateralism Strategy - Anggraheni, Palupi; Diaz, Yohana Grezia; Putri, Athaya Aulia (POLITEA, 2023)
The emergence of culture currently being acknowledged in political science. It has played an important role in policy making to the development of a region or country.  This paper will focus on how far culture, especially local values, has been interpreted in the decision-making process of foreign policy. Culture and its values and interpretation exists in formal organizations whose members develop a form of shared belief, shared values, and shared knowledge to interpret the reality. Indonesia is famous for its identity to remain neutral as one of the nation's foreign policy blueprint. The long-standing foreign policy of mendayung antara dua karang is challenged several times, especially during the shift of the unipolar through multipolar system in world order. This research will highlight the role of culture in foreign policy by interpreting local values, especially Javanese values conducted by President Joko Widodo’s cabinet in foreign policy approaches related to G20 chairmanship by Indonesia. By using constructivism approach in foreign policy and non-western approach in international relations, this research found that under President Jokowi’s administration there are attempts to re-interpreting Javanese values such as rukun, which emphasize on harmonious values in conducting foreign policy.